Learning Interest: How Does The Experimentation of the Team Games Tournament Learning Models? - Alfina Amalia Azizah; Fintia Monica Sari; Helvita Helvita; Hilda Aulia Zahra; Ines Putri Nirwani; Nurul Azizah (PT. Pusmedia Group Indonesia, 2025)
The low interest in learning of students, especially in terms of involvement and interest in learning, is the background of this study. This study aims to determine the effect of the Teams Games Tournament (TGT) learning model on students' interest in learning in the subject of Islamic Religious Education (PAI) in class VIII of SMP Negeri 23 Bandar Lampung. This study uses a quasi-experimental quasi-quantitative technique. The sample consists of two classes, namely the experimental class with the TGT model and the control class with conventional learning. The basic random sampling method can be used with the spin-the-wheel program. With a significance value of the TGT class of 0.04 ± 0.05, the normality test shows from the results of the study that the experimental and control classes are normally distributed. The homogeneity test produces homogeneous data and the results are 0.341> 0.05. Data were obtained through a questionnaire and t-test analysis was carried out. The results showed that students in both classes had slightly different learning interests; Students who studied with the TGT approach showed higher enthusiasm in learning. Thus, the TGT model helps increase junior high school students' curiosity about PAI.